Industrial training report: Windrunner Global Sdn Bhd - Ruslan, Muhammad Syafiq (Universiti Teknologi MARA, Perlis, 2024)
This industrial training report states a comprehensive summary of my contribution and accomplishments during my six-month internship at Windrunner Global Sdn Bhd starting from 1 March 2024 to 9 August 2024. In this report, I need to explain the company profile which are the company background, vision and mission, objectives, and organizational chart. Besides, I also need to provide training reflection. During my internship, I was assigned to support the creative and marketing departments. In this team, I need to do a task that is market research, content creation, event management, and customer engagement. I gained invaluable insight into the meaning of teamwork, effective communication, and innovative problem-solving in a dynamic marketing environment. The advice and assistance provided by experienced staff have significantly influenced my approach to marketing and business strategy. The internship at Windrunner Global has been an outstanding experience, giving me comprehensive knowledge and direct exposure to various areas of marketing strategies and operations. Moreover, I need to conduct a SWOT analysis and recommendation to help the company determine its core strengths and areas of success, as well as the weaknesses that need to be solved. In addition, analyses opportunities for development and expansion as well as threats from competitors, changing markets, or economic instability.